2010
DOI: 10.1007/s11703-009-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram and heavy metal resistance of pathogenic bacteria isolated from moribund cage cultured silver catfish (Pangasius sutchi) and red hybrid tilapia (Tilapia sp.)

Abstract: Antibiogram and heavy metal resistance of pathogenic bacteria isolated from moribund cage cultured silver catfish (Pangasius sutchi) and red hybrid tilapia (Tilapia sp.)Abstract Antibiogram and heavy metal resistance patterns of pathogenic bacteria isolated from moribund cage cultured silver catfish (Pangasius sutchi) and red hybrid tilapia (Tilapia sp.) from Sungai Manir, Terengganu, Malaysia were studied and characterized. Sungai Manir is one of the famous rivers in Terengganu for its wide variety of cage cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
(13 reference statements)
1
7
0
Order By: Relevance
“…Antibiotic susceptible test was performed using disk diffusion method [ 1 ]. The bacterial cells were prepared by propagated the bacteria using Luria Broth (Oxoid, England), followed by centrifugation at 14,500 rpm for 10 min using MiniSpin (Eppendorf, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic susceptible test was performed using disk diffusion method [ 1 ]. The bacterial cells were prepared by propagated the bacteria using Luria Broth (Oxoid, England), followed by centrifugation at 14,500 rpm for 10 min using MiniSpin (Eppendorf, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A. hydrophila and E. tarda were successfully isolated from moribund cage cultured silver catfish ( Pangasius sutchi ), striped catfish ( Pangasianodon hypophthalmus ), and red hybrid tilapia ( Tilapia spp.) [ 1 , 2 ]. According to Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…At the preprocessing stage, Vibrio was not detected in catfish intestinal contents (65). However, in a more recent study 15 antibiotic-resistant Vibrio colonies were isolated from the internal organs of 100 silver catfish in Malaysia (57). In another study of 240 catfish fillets taken from three processing plants during 1 year, seasonal variation in V. cholerae prevalence was documented; 27.5% of fillet samples (33 of 120) taken during the summer and fall were positive for V. cholera, but none of the 120 fillet samples taken in the winter and spring were positive for this microorganism (40).…”
Section: Microbial Hazards Associated With Catfish Consumptionmentioning
confidence: 97%
“…Salmonella isolated from catfish imported to the United States from Thailand were resistant to a variety of antibiotics, including nalidixic acid, streptomycin, tetracycline, and kanamycin (139). In a more recent study, 11 antibiotic-resistant Salmonella colonies were isolated from the internal organs of 100 silver catfish (Pangasius sutchi) obtained in Malaysia (57). These data imply that catfish are exposed to antibiotics that might affect bacterial resistance patterns.…”
Section: Microbial Hazards Associated With Catfish Consumptionmentioning
confidence: 99%
“…A study in Terengganu River, Malaysia, revealed the multiple antibiotic resistance of bacteria which indicated that the cage-cultured silver catfish, Pangasius sutchi (Fowler) and red hybrid tilapia there were under high exposure to the several antibiotics, including streptomycin, amoxicillin, chloramphenicol, erythromycin, ampicillin, sulfamethoxazole and tetracycline (Lee et al 2010). Interestingly, their study area was at the same river with our present study.…”
mentioning
confidence: 99%